(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
As a foundation for project planning, execution, and supervision, management may use the Project Evaluation and Review Technique (PERT) and the Critical Route Method (CPM) to discover the longest time consuming, or consuming, path across a network of tasks or activities. The solutions assist managers in maximizing the shortest time period feasible in order to save project costs and time in half. The use of project planning on the construction of railway lines is shown in this study article, which uses two project management methodologies. To demonstrate the logical sequence of actions to be undertaken in this research paper in order to fulfill this article’s purpose, I used the Project Evaluation and Review Technique (PERT) and the Critical Path Method (CPM). The benefits of utilizing CPM scheduling to build railway tracks are discussed in this work. According to the results, the construction may be completed in 852 days rather than the 900 days initially projected, saving roughly 6%. This will show up the network diagram together with beginning and completion timings with the list of activities related with the target in an effective method so as to accomplish the building on or before a defined time limit with required quality standard.